Space verification experimental analysis for attitude control of a tethered space robot - Masahiro NOHMI (Nihon Kikai Gakkai ronbunshu, 2014)
This paper describes evaluation analysis for the space verification experiment of a tethered space robot on the sounding rocket "S-520-25." The S-520-25 rocket was launched on August 31, 2010. The tether was extended and kept its tension, and attitude control of the tethered space robot was performed. However, experimental results included non-linear dynamic motion, though the attitude control is designed under assumption of linear motion. Then, the space experimental results have been examined by mechanical dynamics software ADAMS. Non-linear motion can be evaluated qualitatively by simulation, and effectiveness of the attitude control has been confirmed.